From tradition to innovation: the cultural-historical vector of educational practices and the socialization of children in contemporary society - Gevorgyan, S.R.; Ispiryan, M.M.; Sargsyan, V.Zh; Tadevosyan, H.V. (Kulʹturno-istoricheskai͡a︡ psikhologii͡a, 2025)
The goal of this study is to explore chess teachers' perceptions of the transformation of childhood in the context of cultural-historical psychology, their views on traditional and innovative aspects of chess education, and their impact on the internalisation of value orientations, as well as on the development of children's socialisation and cognitive functions. Methods. The empirical part of the study is based on a survey of 104 chess teachers working in Armenian schools. Both quantitative methods (factor and correlation analysis) and qualitative methods (content analysis of open-ended responses) were employed. Particular attention is given to how teachers themselves perceive developmental changes in children, the transformation of value orientations, and their own role in fostering children's agency. The results. Teachers view chess as a symbolic activity through which children learn to plan, forecast, and analyze the consequences of their decisions-thus acquiring essential cross-curricular skills. Цель исследования - выявить представления преподавателей шахмат о трансформации детства в свете культурно-исторической психологии, их восприятие традиционных и инновационных аспектов шахматного образования и их влияние на интериоризацию ценностей, развитие социализации и когнитивных функций у детей. Методы. Эмпирическая часть исследования построена на анкетировании 104 учителей шахмат в армянских школах. Были применены как количественные методы (факторный и корреляционный анализы), так и качественные (контент-анализ открытых ответов). Отдельное внимание уделяется тому, как сами педагоги осознают изменения, происходящие в детском возрасте, трансформации ценностных установок, а также свое участие в развитии субъектной позиции у ребенка. Результаты: Шахматы воспринимаются учителями как знаковая деятельность, в которой ребенок учится планировать, прогнозировать, анализировать последствия своих решений - т. е. формирует базовые метапредметные навыки. Выводы. Восприятие шахмат как образовательной практики тесно связано с возрастом, стилем преподавания и личным педагогическим опытом, подтверждается количественными данными, полученными с помощью факторного и корреляционного анализа. Преподаватели воспринимают шахматы не только как инструмент интеллектуального развития, но и как средство формирования личностных, нравственных и педагогических качеств.